EFFECT OF FAIR VALUE ACCOUNTING ON FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2023)
This study ascertained the effect of fair value accounting on the financial performance of deposit money banks in Nigeria for the period 2012-2022. Using Ex-Post Facto research design, the data were generated from annual accounts of the selected sampled banks. Regression analysis was employed to test the hypotheses. Based on the outcome from the analysis, the study found that fair value accounting has significantly effects return on equity of deposit money banks in Nigeria at 5% level of significance, the study also revealed that fair value accounting has no significant effects profitability of deposit money banks in Nigeria at 5% level of significance. Based on the findings and conclusion of this study, it is therefore recommended among others that managers of listed deposit money banks in Nigeria should engage in activities that upsurge their revenue as this increases the value of shares.
Keywords: Fair value accounting; Return on equity; Profitability